Optimasi Algoritme Xtreme Gradient Boosting (XGBoost) pada Harga Saham PT. United Tractors Tbk. - Astutiningsih, Tiyas; Saputro, Dewi Retno Sari; Sutanto (SPECTA Journal of Technology, 2023)
The issue of a recession in 2023 continues to increase, affecting the rise and fall of the stock price index. From 2015 to 2023 the share price of PT. United Tractors Tbk. experiencing fluctuations. The method used to determine fluctuations in PT. United Tractors Tbk. share data is an ensemble learning. One of the ensemble learning algorithms that is popular and often used for prediction or classification problems is Extreme Gradient Boosting (XGBoost). The aim of this research is to obtain the best model ofPT. United Tractors share prices using XGBoost. XGBoost is a development of Gradient Boosting which has the advantage of faster implementation. The data used is the share price of PT. United Tractors Tbk. from March 16 2021 to March 31, 2023. This research uses four technical indicators in analyzing share price movements, namely Exponential Moving Average (EMA), Simple Moving Average (SMA), Relative Strength Index (RSI) and Moving Average Convergence /Divergence (MACD). This experiment produced a MAPE value of 3.89%, which shows the optimization of the XGBoost algorithm on PT share prices. United Tractor Tbk. produces accurate models.